PREDICTIVE ROLE OF PERSONALITY TRAITS ON INTERNET ADDICTION - Celik, Serkan; Atak, Hasan; Basal, Ahmet (ANADOLU UNIV, 2012)
Aiming to develop a model seeking to investigate the direct effects of personality types on internet addiction, this study was set and tested on tertiary level students receiving education within two learning modes: face to face and distance education. The participants of the study, selected through maximum variety method within purposive sampling, included 210 students enrolled on face-to-face and distance education programs of computer programming department. In addition to a personal data form aiming to obtain information on demographic features of the participants, a personality inventory and an Internet addiction scale were utilized to gather data. As an analysis model concurrently exerting both the mediation and direct effects, path analysis with observed variables was utilized in the current study to test the developed model. The findings revealed that while the most powerful predictor variable of internet addiction was conscientiousness, openness to experience was found as the weakest independent variable predictor. Additionally the developed model was observed as valid for both face to face and distance education students.
Keywords: Internet addiction; distance education; personality; COLLEGE-STUDENTS; 5-FACTOR MODEL; ADOLESCENTS; LONELINESS; ONLINE; PEER; Education & Educational Research